2023
DOI: 10.1021/acs.langmuir.2c03367
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Noble Metal High-Entropy Alloy Nanofilms by Atomic Layer Deposition for an Enhanced Hydrogen Evolution Reaction

Abstract: The current synthesis methods of high-entropy alloy (HEA) thin-film coatings face huge challenges in facile preparation, precise thickness control, conformal integration, and affordability. These challenges are more specific and noteworthy for noble metal-based HEA thin films where the conventional sputtering methods encounter thickness control and high-cost issues (high-purity noble metal targets required). Herein, for the first time, we report a facile and controllable synthesis process of quinary HEA coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…(d) Acidic stability tests of different low dimension HEA catalysts. Alkaline data was obtained from refs and acidic data from refs , , , , and .…”
Section: Nanosized Heasmentioning
confidence: 99%
“…(d) Acidic stability tests of different low dimension HEA catalysts. Alkaline data was obtained from refs and acidic data from refs , , , , and .…”
Section: Nanosized Heasmentioning
confidence: 99%
“…High-entropy alloys (HEAs) and their nitrides (HENs) are recently discovered structural [ 1 ] and functional [ 2 ] materials that are already involved in the development of many new and important high-tech applications [ 3 , 4 ] due to their outstanding properties such as hardness and strength [ 5 , 6 ], fatigue resistance [ 7 , 8 ], fracture toughness [ 9 ], high-temperature oxidation resistance [ 10 , 11 ], corrosion resistance [ 12 , 13 ], and electrical and magnetic properties [ 14 , 15 ]. These HEA properties have been attributed to four effects: (a) the high entropy, offering the thermodynamics for stabilizing the simple structure; (b) the sluggish diffusion effect, which slows the growth of second phase nuclei out of a single-phase solid solution; (c) the severe lattice distortion due to the presence of atoms having different radii, which provides excess strength and contributes to the slow kinetics in HEAs; and (d) the cocktail effect, which could synergistically enhance the properties by alloying [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many high-tech applications in the nuclear industry, photocatalysis, or corrosion protection [ 3 , 4 , 12 , 13 , 22 , 23 , 24 , 25 , 26 ] require the use of thin films, which also have cost benefits, since some elements used in HEA are rather expensive. HEA and HEN thin films were deposited by magnetron sputtering [ 22 ] or pulsed laser deposition (PLD) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The unique structural stability of HEA arises from a combination of the high entropy effect and sluggish diffusion effect, driven by the variations in the atomic radii of the constituent elements and their highly disordered arrangement in the systems. [14][15][16] Notably, noble metal-based HEAs (NM-HEAs) consisting of Pt, Pd, Rh, Ru, and Ir exhibit superior activity owing to their modied electronic structure, which has been demonstrated through both experimental [17][18][19][20] and simulation [21][22][23] studies. For example, Wu et al demonstrated the broad and continuous valence band of the IrPdPtRhRu HEA, indicating the diverse localized density of states.…”
Section: Introductionmentioning
confidence: 99%
“…[36][37][38] As such, the morphology of the deposited thin lm usually exhibits nanoparticle-like features, which has been observed in numerous studies on ALD-made thin lms. 19,[39][40][41][42][43][44][45][46][47] Therefore, the NM-HEA thin lm deposited by ALD could expose an enlarged surface area. Nonetheless, the complexity of materials deposited by ALD is constrained by the limited deposition temperature window permissible for the deposition of various metals.…”
Section: Introductionmentioning
confidence: 99%